O papel do score de cálcio coronário na decisão da terapêutica com estatina em prevenção primária - uma revisão sistemática - Pedro Almeida Poças (2021)
INTRODUCTION AND OBJECTIVES Cardiovascular prevention is a cornerstone in atherosclerotic disease approach. The coronary calcium score (CCS) is a marker of subclinical disease, presenting a good correlation with atherosclerotic burden and with a recognised prognostic value. It has been suggested that it could also guide the therapeutic decisions regarding statins in primary prevention settings and, thus, we believe this topic deserves further discussion. Our main aim is to understand if the intervention with statin, guided by CCS, will have impact on the risk of cardiovascular events and mortality. METHODS MEDLINE/PubMED, Web of Science and ClinicalTrials.gov were searched for the last time in February 2021. Retrieved papers, reviews and trial registries were hand-searched, selected and extracted information by two independent authors. We included clinical trials and observational studies in asymptomatic samples, submitted to evaluation of CCS by computed tomography (CT), in which the outcomes were cardiovascular or all-cause mortality or cardiovascular events. RESULTS Nine studies with 61 388 participants were included, with median follow-up between 2,5 and 12 years. Results pointed to a raise in all-cause mortality and cardiovascular events risk with the CCS strata, in a proportional graded fashion. The number needed to treat with statin decreases significantly with CCS rise, mostly when comparing the CCS 0 vs > 100. The majority of evidence with statin intervention or exposure confirmed a significant event risk reduction when using a CCS > 100 threshold. Altogether, these results support the use of this threshold (CCS of 100) to define the group of patients in which the therapeutic benefit with statin, in primary prevention, would be superior. CONCLUSIONS CCS has proven to be a good prognostic marker. We believe that it could have a more relevant role in stratifying the therapeutic decision with statins in patients in primary prevention.